Development of conventional and real-time multiplex PCR assays for the detection of nosocomial pathogens - Anbazhagan,Deepa (2011)
Nosocomial infections are major clinical threats to hospitalised patients and represent an important source of morbidity and mortality. It is necessary to develop rapid detection assays of nosocomial pathogens for better prognosis and initiation of antimicrobial therapy in patients. In this study, we present the development of molecular methods for the detection of six common nosocomial pathogens including Escherichia coli, Staphylococcus aureus, Streptococcus pneumoniae, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter spp. Conventional multiplex PCR and SYBR Green based real time PCR assays were performed using genus and species specific primers. Blind testing with 300 clinical samples was also carried out. The two assays were found to be sensitive and specific. Eubacterial PCR assay exhibited positive results for 46 clinical isolates from which 43 samples were detected by real time PCR assay. The sensitivity of the assay is about 93.7% in blind test isolates. The PCR results were reconfirmed using the conventional culture method. This assay has the potential to be a rapid, accurate and highly sensitive molecular diagnostic tool for simultaneous detection of Escherichia coli, Staphylococcus aureus, Streptococcus pneumoniae, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter spp. This assay has the potential to detect nosocomial pathogens within 5 to 6 hours, helping to initiate infection control measures and appropriate treatment in paediatric and elderly (old aged) patients, pre-and post surgery patients and organ transplant patients and thus reduces their hospitalization duration .